2018
DOI: 10.3389/fmicb.2018.00551
|View full text |Cite
|
Sign up to set email alerts
|

The Applied Development of a Tiered Multilocus Sequence Typing (MLST) Scheme for Dichelobacter nodosus

Abstract: Dichelobacter nodosus (D. nodosus) is the causative pathogen of ovine footrot, a disease that has a significant welfare and financial impact on the global sheep industry. Previous studies into the phylogenetics of D. nodosus have focused on Australia and Scandinavia, meaning the current diversity in the United Kingdom (U.K.) population and its relationship globally, is poorly understood. Numerous epidemiological methods are available for bacterial typing; however, few account for whole genome diversity or prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 40 publications
(66 reference statements)
0
16
0
Order By: Relevance
“…Microreact is a web tool developed to produce these visualisations and the site provides a means for data to be automatically uploaded from other resources, such as PubMLST 62 . This can be demonstrated using data from a recent paper describing the development of a MLST scheme for Dichelobacter nodosus , the causative agent of ovine footrot, that indicated that the global bacterial population was geographically structured 36 . All isolates that included a genome record in the D. nodosus PubMLST database (n=171) were selected and the Microreact analysis run using cgMLST loci.…”
Section: Use Casesmentioning
confidence: 99%
“…Microreact is a web tool developed to produce these visualisations and the site provides a means for data to be automatically uploaded from other resources, such as PubMLST 62 . This can be demonstrated using data from a recent paper describing the development of a MLST scheme for Dichelobacter nodosus , the causative agent of ovine footrot, that indicated that the global bacterial population was geographically structured 36 . All isolates that included a genome record in the D. nodosus PubMLST database (n=171) were selected and the Microreact analysis run using cgMLST loci.…”
Section: Use Casesmentioning
confidence: 99%
“…The bacterial isolation, DNA isolation, sequencing and analysis of sequence data in this study are as described previously in (Blanchard et al, 2018). A total of 2,126 Interdigital swabs (E-swabs 480CE, Copan U.S.A.) were taken from ewes and lambs.…”
Section: Bacterial Isolationmentioning
confidence: 99%
“…As described by (Blanchard et al, 2018), DNA was isolated using the Qiagen Cador Pathogen Mini Kit, following the manufacturers guidelines and eluted in 60 µl of elution buffer. DNA was sent to MicrobesNG (Birmingham University, U.K.), for sequencing using the Illumina MiSeq at 2 × 250 bp [Raw data is available in the Short Read Archive (PRJNA386733)].…”
Section: Dna Isolation and Sequencingmentioning
confidence: 99%
See 2 more Smart Citations